2018
DOI: 10.3390/rs10060969
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Convective Rainfall Properties and Antecedent Soil Moisture Heterogeneity Conditions in North Africa

Abstract: Abstract:Recent observational studies have demonstrated the relevance of soil moisture heterogeneity and the associated thermally-induced circulation on deep convection and rainfall triggering. However, whether this dynamical mechanism further influences rainfall properties-such as rain volume or timing-has yet to be confirmed by observational data. Here, we analyze 10 years of satellite-based sub-daily soil moisture and precipitation records and explore the potential of strong spatial gradients in morning soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…Rain rates are not directly coupled between model domains in official distributions where only the feedback of the prognostic variables (horizontal and vertical wind, virtual potential temperature, total air density, specific humidity, cloud water and cloud ice) is active. For the West African domain this feedback for precipitation in EXPLC simulations was introduced in order to not only affect atmospheric dynamics but also soil moisture, which directly influences the initiation of deep convection in this region 35 .…”
Section: Methodsmentioning
confidence: 99%
“…Rain rates are not directly coupled between model domains in official distributions where only the feedback of the prognostic variables (horizontal and vertical wind, virtual potential temperature, total air density, specific humidity, cloud water and cloud ice) is active. For the West African domain this feedback for precipitation in EXPLC simulations was introduced in order to not only affect atmospheric dynamics but also soil moisture, which directly influences the initiation of deep convection in this region 35 .…”
Section: Methodsmentioning
confidence: 99%
“…In reality, spatial variability may also be induced by variations in surface conditions. Many observational studies in recent years have highlighted the importance of surface heterogeneity for the triggering and development of convection (e.g., Taylor et al, 2011; Petrova et al, 2018; Fast et al, 2019). Differential heating patterns at the surface generate horizontal pressure gradients, which induce horizontal flows from cool/wet to warm/dry surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Some land–atmosphere interaction studies have been carried out at the inter‐annual and intra‐seasonal time scale in this region (Ruscica et al ., 2014; 2015; 2016; Spennemann et al ., 2018; Menéndez et al ., 2019); however, many land–atmosphere processes are still poorly understood, mainly at the diurnal scale and especially how they influence precipitation. In general, global and regional studies have found that the coupling seems to favour afternoon precipitation preferably over strong soil moisture gradients (Taylor et al ., 2011; Petrova et al ., 2018), but its magnitude and the signal of the feedbacks can change depending on the background wind (Froidevaux et al ., 2014; Ford et al ., 2015; Holgate et al ., 2019) and the moisture flux convergence (Petrova et al ., 2018; Welty and Zeng, 2018). Moreover, the coupling can be strong in certain synoptic/mesoscale situations but weak or non‐existent in the overall mean (Song et al ., 2016; Welty and Zeng, 2018), and it can vary widely depending on the type of dataset analysed (observation‐derived products, models, reanalyses, etc.…”
Section: Introductionmentioning
confidence: 99%